2012
DOI: 10.2135/cropsci2011.06.0297
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection in Plant Breeding: A Comparison of Models

Abstract: Simulation and empirical studies of genomic selection (GS) show accuracies sufficient to generate rapid genetic gains. However, with the increased popularity of GS approaches, numerous models have been proposed and no comparative analysis is available to identify the most promising ones. Using eight wheat {Triti-cum aestivum L.), barley {Hordeum vulgäre L.), Arabidopsis thaliana (L.) Heynh., and maize {Zea mays L.) datasets, the predictive ability of currently available GS models along with several machine lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
548
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(588 citation statements)
references
References 49 publications
35
548
3
2
Order By: Relevance
“…Previous genome-wide association mapping studies suggested presence of epistatic effects for FHB resistance . Thus, it is tempting to speculate that RKHSR outperforms RR-BLUP and Bayes-Cπ as observed in several previous genomic selection studies (Crossa et al, , 2011de los Campos et al, 2010;Heslot et al, 2012). In contrast to this expectation, however, no significant differences among the accuracies of the three applied genomic selection models were observed (Table 3).…”
Section: Figurementioning
confidence: 67%
“…Previous genome-wide association mapping studies suggested presence of epistatic effects for FHB resistance . Thus, it is tempting to speculate that RKHSR outperforms RR-BLUP and Bayes-Cπ as observed in several previous genomic selection studies (Crossa et al, , 2011de los Campos et al, 2010;Heslot et al, 2012). In contrast to this expectation, however, no significant differences among the accuracies of the three applied genomic selection models were observed (Table 3).…”
Section: Figurementioning
confidence: 67%
“…It has been shown that RKHS can outperform linear models in predictive ability in chickens (Gonzá lez-Recio et al, 2008) and plants Gonzá lez-Camacho et al, 2012). Heslot et al (2012) compared the predictive performance of different linear and non-linear GS models for several traits in plants and found that, overall, linear and non-linear models performed similarly. RKHS seemingly gave the best predictive ability: for example, in 16 out of their 18 comparisons RKHS outperformed Bayes Cp (Habier et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The estimated marker effects are then applied to predict the breeding value of nonphenotyped individuals based on their molecular marker profiles. The great potential of genomic selection for complex traits has been demonstrated in several experimental studies in plant and animal breeding populations (Bernardo, 2008;Heffner et al, 2009;Heslot et al, 2012;Massman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One crucial challenge in genomic selection is to choose the appropriate biometrical model (Heffner et al, 2009;Heslot et al, 2012). The relative performance of biometrical models is expected to depend on the genetic architecture of the traits under scrutiny.…”
Section: Introductionmentioning
confidence: 99%